Results of surgical treatment patients elderly and old age with perforation of stomach and duodenal ulcer - Danyliuk, M. B.; Zavhorodniy, C. M.; Rylov, A. I.; Kubrak, M. A.; Данилюк, Михайло Богданович; Завгородній, Сергій Миколайович; Кубрак, Михайло Анатолійович (My University, 2023)
The article is devoted to the issues of gastric and duodenal ulcer perforation. Despite modern pharmacological advances in the treatment of peptic ulcer disease, the incidence of complicated ulcers remains high. This problem is especially true for elderly and senile patients. Therefore, our work aimed to evaluate the results of surgical treatment of gastric and duodenal ulcer perforation in elderly and senile patients. The study was based on the analysis of the results of both surgical treatment and perioperative conservative therapy in elderly and senile patients with gastric or duodenal ulcer perforation. The study included 65 patients with this diagnosis. Based on our analysis, we determined that surgical treatment of perforated gastric and duodenal ulcers in the elderly and senile is a difficult task. 40.0% of patients, or 26 patients, were hospitalised later than 12 hours after the onset of the disease. Such a delayed onset of the disease has a negative impact on the general condition of patients and treatment outcomes. An important factor in treating this age group is that 89.2% have comorbidities in addition to the main disease. The duration of the disease, the severity of the general condition and a significant number of comorbidities lead to a high incidence of postoperative complications - 72.3% and mortality in 38.5% of patients. In conclusion, elderly and senile patients represent a particular category of patients that requires individualised approaches and modification of treatment standards. In turn, it will improve treatment outcomes and thereby reduce the incidence of postoperative complications and mortality.
Keywords: perforated ulcer; peritonitis; elderly people